Superkid in training - Allison, Jennifer (Iggy Loomis, 2013)
Just as Daniel is adjusting to sharing his room with Iggy, his little brother, a strange boy with a big interest in bugs moves into their neighborhood, providing Daniel with a new friend but Iggy with some mutated DNA.